Effect of Temperature on Pyrolysis Oil Using High-Density Polyethylene and Polyethylene Terephthalate Sources From Mobile Pyrolysis Plant - Prurapark, Ruktai; Owjaraen, Kittwat; Saengphrom, Bordin; Limthongtip, Inpitcha; Tongam, Nopparat (Frontiers in Energy Research, 2020)
This research aims to study the effect of temperature, collecting time, and condensers on properties of pyrolysis oil. The research was done be analyzing viscosity, density, proportion of pyrolysis products and performance of each condenser towers for the pyrolysis of high-density polyethylene (HDPE) and polyethylene terephthalate (PET) in the mobile pyrolysis plant. Results showed that the main product of HDPE resin was liquid, and the main product of PET resin was solid. Since the pyrolysis of PET results in mostly solid which blocked up the pipe, the analysis of pyrolysis oil would be from the use of HDPE as a raw material. The pyrolysis of HDPE resin in the amount of 100 kg at 400, 425, and 450°C produced the amount of oil 22.5, 27, and 40.5 L, respectively. The study found that 450°C was the temperature that gives the highest amount of pyrolysis oil in the experiment. The viscosity was in the range of 3.287–4.850 cSt. The density was in the range of 0.668–0.740 kg/L. The viscosity and density were increased according to three factors: high pyrolysis temperature, number of condensers and longer sampling time. From the distillation at temperatures below 65, 65–170, 170–250, and above 250°C, all refined products in each temperature range had the carbon number according to their boiling points. The distillation of pyrolysis oil in this experiment provided high amount of kerosene, followed by gasoline and diesel.